Comparison of Laser Doppler Imaging (LDI) and clinical assessment in differentiating between superficial and deep partial thickness burn wounds. Issue 2 (March 2018) - Jan, Saadia Nosheen; Khan, Farid Ahmed; Bashir, Muhammad Mustehsan; Nasir, Muneeb; Ansari, Hamid Hussain; Shami, Hussan Birkhez; Nazir, Umer; Hanif, Asif; Sohail, Muhammad
Highlights: Laser Doppler Imaging (LDI) and clinical assessment compared for gauging burn depth. Management of superficial and deep partial burns different. Accurate assessment of burn depth allows pertinent treatment with better outcomes. LDI better diagnosed burn depth though clinical appraisal was better than previous studies. High burn patient influx and greater clinical experience contributed to the result. Abstract: Purpose of presentation/study: To compare the accuracy of Laser Doppler Imaging (LDI) and clinical assessment in differentiating between superficial and deep partial thickness burns to decide whether early tangential excision and grafting or conservative management should be employed to optimize burn and patient management. Study period: March 2015 to November 2016. Methods/procedure details: Ninety two wounds in 34 patients reporting within 5 days of less than 40% burn surface area were included. Unstable patients, pregnant females and those who expired were excluded. The wounds were clinically assessed and LDI done concomitantly Plastic Surgeons blinded to each other's findings. Wound appearance, color, blanching, pain, hair follicle dislodgement were the clinical parameters that distinguished between superficial and deep partial thickness burns. On day 21, the wounds were again assessed for the presence of healing by the same plastic surgeons. The findings were correlated with the initial findings on LDI and clinical assessment and the results statistically analyzed. Results/outcome: The data of 92 burn wounds was analyzed using SPSS (ver. 17). Clinical assessment correctly identified the depth of 75 and LDI 83 wounds, giving diagnostic accuracies of 81.52% and 90.21% respectively. The sensitivity of clinical assessment was 81% and of LDI 92.75%, whereas the specificity was 82% for both. The positive predictive value was 93% for clinical assessment and 94% for LDI while the negative predictive value was 59% and 79% respectively. Conclusions: Predictive accuracy of LDI was found to be better than clinical assessment in the prediction of wound healing, the gold standard for wound healing being 21 days. As such it can prove to be a reliable and viable cost effective alternative per se to clinical assessment.